Structural Dependence and Attitudinal Divergence: A Comparative Analysis of Nuclear Power Acceptance between Highly- and Lowly-Nuclear-Power-Dependent Countries in Europe - Song, Jangchul; Kim, Seoyong; Koo, Bonjun (European Public & Social Innovation Review, 2026)
Introduction: Nuclear energy remains one of the most contested energy sources globally, and public acceptance is critical for energy policymakers. This study addresses a gap in the literature by comparing public acceptance between Highly-Nuclear-Power-Dependent Countries (HNPDCs) and Lowly-Nuclear-Power-Dependent Countries (LNPDCs) in Europe. Methodology: Using Eurobarometer 72.2 data (2009, N = 26,663; 27 EU member states), we conducted OLS regression analyses for each group, supplemented by country-level macro-indicator comparisons. HNPDCs are defined as countries where nuclear power exceeds 30% of total electricity production. Results: Perceived benefit and trust are the strongest positive predictors of nuclear acceptance; perceived risk exerts the strongest negative effect in both groups. In HNPDCs, proximity to a nuclear facility and self-assessed information level significantly predict acceptance; in LNPDCs, educational attainment plays a more prominent role. Discussion: Nuclear dependency shapes distinct cognitive pathways for attitude formation. HNPDCs exhibit higher acceptance, higher perceived risk and benefit, and stronger trust, yet also greater organized environmental opposition. Conclusions: Nuclear dependency shapes both the level and determinant structure of public attitudes, with important implications for context-sensitive energy communication strategies.